Factors Influencing Customers Repurchase And Willingness To Pay More In Live Streaming Commerce The Moderating Effect Of Emotional Attachment - Li, Chao (2024)
Since the advent of advanced Internet technology, live streaming has become a pivotal tool for brands and sellers to amplify sales and foster customer engagement. The competitive landscape of live streaming commerce has led to extensive research into factors influencing customer motivation, purchasing intent, impulsive buying, and engagement in this context. However, the critical role of emotions, stemming from the interaction between streamers and customers, has often been overlooked. This study specifically focused on the role of emotional satisfaction and its drivers in live streaming commerce, particularly regarding the subsequent impact on customer repurchase behavior and willingness to spend more in live streaming channels. Employing the Stimulus-Organism-Behavior-Consequence (SOBC) framework and the Source Credibility Theory, this study hypothesizes that the characteristics of streamers, platforms, products, and social aspects were hypothesized as stimuli influencing consumers’ emotional satisfaction during live streaming shopping experience. Moreover, this study has explored the moderating effect of consumers’ emotional attachment in repurchase behavior and willingness to spend more in live streaming channels. This research employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) as the analytical tool. A comprehensive online survey involving 521 participants was executed, culminating in 506 valid responses after outlier removal.